Meje katastrskih občin pod Krimom: po sledeh meje med Bistro in Engelshausi iz leta 1726 (= The cadastral municipality boundaries under Krim: the boundary between Bistra and Engelshaus from 1726) - Mihaela Triglav Čekada (Geodetski Vestnik, 2023)
The borders of the cadastral municipalities that are still valid today are, in many cases, based on much older landowners’ borders of feudal lordships. Thus, in central Slovenia, in the forests below Mount Krim, we find the old boundary marks representing today’s cadastral municipality of Preserje, based on the former border between the Carthusia Bistra and the Ig estate from 1726. The main purpose of this paper is to present the current state of the preserved boundary marks along this border. The preserved boundary marks are about 80 cm high, have carved sequential letters, the year 1726 and coats of arms of the Carthusia Bistra and the earls Engelshaus (the owners of the Ig estate at that time). In 1748, this boundary was adopted as the boundary between the Notranjska (Inner) and the Gorenjska (Upper) districts of the Carniola region in the Habsburg Monarchy. As part of the Franciscan cadastral survey in 1823, this border was used as the border of cadastral municipalities, and it has retained this role until today. On the Franciscan cadastral maps, we find eleven locations numbered with the year 1726 and the consecutive letter from B to M. Today, at these locations, we can still find two original boundary marks decorated with coats of arms and the year 1726, two destroyed original boundary marks and three probably later replaced boundary marks without inscriptions and coats of arms. We also examined locations on the even older eastern border of the Carthusia Bistra, on which today mainly only post-war trigonometric points of lower orders can be found; only on the Smrekovec hill under Rakitna did we find another older boundary mark without additional inscriptions or coats of arms.